Tetracycline antibiotics - Ramachanderan, Raghavendra; Schäfer, Bernd (ChemTexts, 2021)
Tetracyclines belong to the first broad-spectrum, well-tolerated, and easy-to-administer antibiotics, which are effective against plague, cholera, typhoid, syphilis, Legionnaire’s disease, and anthrax. Some can also be used to treat malaria, Lyme disease, tuberculosis, Rocky Mountain spotted fever, and leprosy. Humans first encountered these chemical species involuntarily in ancient times, as evidenced from the analysis of bone samples dating back more than 1500 years. Shortly after World War II, they were “rediscovered” at Lederle Laboratories and Pfizer as a result of an intense search for new antibiotics. Their bacteriostatic action is based on the inhibition of protein biosynthesis. Since the structure elucidation by Robert Woodward, Lloyd Hillyard Conover, and others in the 1950s, tetracyclines have become preferred targets for natural product synthesis. However, on industrial scale, they became readily available by fermentation and partial synthesis. Their casual and thoughtless use in the initial decades after launch not only in humans but for veterinary purposes and as growth-enhancement agents in meat production rapidly led to the emergence of resistance. In an arms race for new antibiotics, more and more new drugs have been developed to deal with the threat. In this ongoing endeavor, a remarkable milestone was set by Andrew Myers in 2005 with the convergent total synthesis of (−)-doxycycline, as well as numerous azatetracyclines and pentacyclines, which has inspired chemists in the pharmaceutical industry to discover novel and highly active tetracyclines in recent years.
Gesehen am 17.04.2023